1974
DOI: 10.1021/jo00925a006
|View full text |Cite
|
Sign up to set email alerts
|

Selective reductions. XX. Stereochemistry of the reduction of cyclic, bicyclic, and polycyclic ketones by dialkylboranes. Simple, convenient procedure for the reduction of ketones to the corresponding alcohols with exceptionally high steric control

Abstract: state, 29, predominant formation of the cis decalin 27 would be expected. As shown for 3 in diagram 21, the Ci equatorial hydrogen bond in 26 is perpendicular to the cyclopropane bond which is adsorbed on the catalyst. Thus, the formation of the olefin 30 could occur by a process similar to that described for the formation of 22. While the product stereochemistry obtained from the hydrogenation of 30 is not available, it has been reported that the hydrogenation of the demethyl compound 31 over platinum in acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…As shown in Figure , the obtained compound could be either endo - 4h or exo - 4h . Based on the related literature, nucleophiles tend to add to norbornanone from the exo side, giving very high diastereoselectivities. , The same also applies to alkynyl-metal reagents. , A combination of 1 H NMR, 13 C NMR, 1 H, 1 H-COSY, 1 H, 13 C-HSQC, and 1 H, 1 H-NOESY spectroscopies (see Supporting Information) leads to the conclusion that the piperidine unit resides on the endo side of the molecule. Because of the complexity of the acquired spectra, our conclusion is not definitive, but in conjunction with the known propensity of nucleophiles to add to norbornanone from the exo side, the data suggest exo alkynylation.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As shown in Figure , the obtained compound could be either endo - 4h or exo - 4h . Based on the related literature, nucleophiles tend to add to norbornanone from the exo side, giving very high diastereoselectivities. , The same also applies to alkynyl-metal reagents. , A combination of 1 H NMR, 13 C NMR, 1 H, 1 H-COSY, 1 H, 13 C-HSQC, and 1 H, 1 H-NOESY spectroscopies (see Supporting Information) leads to the conclusion that the piperidine unit resides on the endo side of the molecule. Because of the complexity of the acquired spectra, our conclusion is not definitive, but in conjunction with the known propensity of nucleophiles to add to norbornanone from the exo side, the data suggest exo alkynylation.…”
Section: Resultsmentioning
confidence: 93%
“…Based on the related literature, nucleophiles tend to add to norbornanone from the exo side, giving very high diastereoselectivities. 18a,60 The same also applies to alkynyl-metal reagents. 61,62 A combination of 1 H NMR, 13 C NMR, 1 H, 1 H-COSY, 1 H, 13 C-HSQC, and 1 H, 1 H-NOESY spectroscopies (see Supporting Information) leads to the conclusion that the piperidine unit resides on the endo side of the molecule.…”
Section: Resultsmentioning
confidence: 98%
“…Several methods have been developed for the stereoselective reduction of ketones, especially substituted cyclohexanones. In general, the thermodynamically less stable axial alcohols arising from an equatorial delivery of the hydride may be accessed by the use of bulky hydride-based reducing agents . In our case, the desired product was the equatorial alcohol, which would be formed via axial delivery of the hydride.…”
Section: Resultsmentioning
confidence: 95%
“…Already, we have demonstrated that microbial hydrolysis of ( ± )-t-2,t-4-dimethyl-r-l-cyclohexyl acetate, followed by the oxidation, gave (-)-(2/?,4/? )-c/s-2,4-dimethyl-l-cyclohexanone (6).2) Here, we describe a synthetic method for chiral trans-2,4-dimethy\-1-cyclohexanone (2) by using the microbiological system. The condensation of 4-methyl-l -cyclohexanone (4) with pyrrolidine gave the enamine 5, which was reacted with methyl iodide to form a stereoisomeric mixture of( + )-2,4-dimethyl-1-cyclohexanones.…”
mentioning
confidence: 99%
“…14% of (±)-cisketone (6 2) Reduction of (+ )-2,4-dimethyl-l-cyclohexanone with K-seleetride. To a stirred solution of (±)-2,4-dimethyl-1-cyclohexanone (1.92 g) in 20ml of dry THF at -30°C was added 28 ml ofa 1 m solution ofK-selectride in THF, stirring being continued for 2 hr.…”
mentioning
confidence: 99%